ChemInform Abstract: Formation of Indoles, Dihydroisoquinolines, and Dihydroquinolines by Ruthenium‐Catalyzed Heterocyclizations. Issue 7 (22nd February 2013) - Varela‐Fernandez, Alejandro; Varela, Jesus A.; Saa, Carlos
Abstract Ru‐catalyzed heterocyclization of alkynyl substituted anilines, benzamides, and benzylamines yields the title heterocycles (II), (IV) and (VI), resp., under mild conditions.